Predicting Real-World Functioning in Schizophrenia: The Relative Contributions of Neurocognition, Functional Capacity, and Negative Symptoms - Yang, Zixu; Lee, Soon Hong; Abdul Rashid, Nur Amirah; See, Yuen Mei; Dauwels, Justin; Tan, Bhing Leet; Lee, Jimmy (Frontiers in Psychiatry, 2021)
Neurocognition and functional capacity are commonly reported predictors of real-world functioning in schizophrenia. However, the additional impact of negative symptoms, specifically its subdomains, i.e. Diminished Expression (DE) and Avolition-Apathy (AA), on real world functioning remains unclear. The current study assessed 58 individuals with schizophrenia. Neurocognition was assessed with the Brief Assessment of Cognition in Schizophrenia (BACS), functional capacity with the UCSD Performance-based Skills Assessment (UPSA-B) and negative symptoms with the Negative Symptom Assessment-16 (NSA-16). Real-world functioning was assessed with the Multnomah Community Ability Scale (MCAS) with employment status as an additional objective outcome. Hierarchical Regressions and sequential logistic regressions were used to examine the associations between the variables of interest. The results showed that global negative symptoms contributed substantial additional variance in predicting MCAS and employment status above and beyond the variance accounted for by neurocognition and functional capacity. In addition, both AA and DE predicted the MCAS after controlling for cognition and functional capacity. Only AA accounted for additional variance in employment status beyond that by UPSA-B. In summary, negative symptoms contributed substantial additional variance in predicting both real-world functioning and employment outcomes after accounting for neurocognition and functional capacity. Our findings emphasize both DE and AA as important treatment targets in functional recovery for people with schizophrenia.